Pemanfaatan Limbah Kotoran Sapi Menjadi Pupuk Organik Kompos Dengan Metode Fermentasi EM4 di Desa Batu Kumbung - Suliartini, Ni Wayan Sri; Ismayanti, Jumratul; Khairina, Khairina; Sintanu, Muh. Andi Wirya; Alvin, Zen (Universitas Mataram, 2024)
Batu Kumbung Village is a village located in Lingsar District, West Lombok Regency which is famous for its extensive agricultural land and the village with the largest number of cattle. The large number of livestock causes serious environmental problems caused by livestock waste that is not managed properly. This service is carried out with the aim of providing information, solutions and practices for managing livestock waste into more useful products such as compost. The making of compost was carried out in June and took place in one of the residents' houses which had a cow shed, and the target of this service was all residents of Batu Kumbung Village who had cattle. Compost is made using the fermentation method using EM4. The materials used are cow dung, straw and apu-apu weed. EM4 (Effective Microorganisms) is a mixture of beneficial microorganisms and can speed up the fermentation process. The addition of straw and apu-apu weed aims to balance the C/N ratio levels in compost fertilizer. Cow dung contains the nutrients 0.33% nitrogen, 0.11% phosphorus, 0.13% potassium and 0.26% calcium which makes cow dung suitable for use as compost. Information regarding the content of cow manure was conveyed to the residents of Batu Kumbung Village by the service team. The process of making compost fertilizer is also practiced directly by the community service team in Batu Kumbung Village. The practice of making compost fertilizer is done by mixing dried cow dung, straw and apu-apu weed, then stirring it and placing it in a pile, after which it is sprayed using EM4 solution. This service can provide information about the content of cow dung as well as solutions for managing cow dung waste into useful products.